Sustainable living conditions in subarctic regions of Sweden - Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 2011)
North of the Arctic Circle in Sweden lies Malmfälten, a region that has been dominated by mining activities for over one hundred years. In this region two small towns are located,Kiruna and Gällivare/Malmberget, where current and future underground mining activities are the cause of land instability that requires relocation of substantial parts of both towns. The circumstances in Malmfälten offer significant research opportunities within the fields of urban and infrastructure planning, construction, operation and maintenance and demolition to address environmental problems that result from urban settlements. Environmental issues that are relevant in this context are e.g. the location of valuable natural areas, and emissions from buildings and infrastructure during construction and use. To develop urban settlements sustainability, there is a need for more sustainable technologies in relation to human and social aspects. Besides the special circumstances in Malmfälten concerning the mining activities, land instability and relocation of urban settlements and citizens, this region is also of interest because of the fact that it is located in the Subarctic. In subarctic regions there are special demands on planning, buildings and infrastructure, concerning design, operation and maintenance due to factors such as cold temperatures, snowfall and permafrost. However, technology alone will not be sufficient. New technical solutions and innovations must be integrated both with planning and implementation processes and with a user perspective in order to put new technologies into practice. Malmfälten has the potential to become a uniquely innovative site for sustainable urban technologies, applications and processes in subarctic regions, as re-envisioning and redevelopment of a complete existing urban system is required there. Furthermore, the economic, social and environmental drivers of change in the case of Malmfälten present many possible future scenarios that could affect the relocation of the towns. This uncertainty, ...